THE STUDY OF E-SPORT AS A SPORT IN TERMS OF SOCIAL ASPECTS, PHYSIOLOGICAL ASPECTS, AND ASPECTS OF SPORTS PHILOSOPHY - Muhamad Ichsan Sabillah; Faza Annasai (Faculty of Sport Science, Universitas Negeri Yogyakarta, 2021)
The purpose of this study is to examine E- Sport in the realm of exercise from an overview of social, physiological, and philosophical aspects of exercise. This study uses literature review research and library research ordinance. The information analysis method uses an information reduction model of 24 posts. This research got the result that out of 10 articles, the articles studied in the social aspect reported agreeing with E- Sport on the contrary, 1 article did not agree. Of the 6 articles studied from the physiological aspect, 2 posts reported agreeing and 4 articles reported disagreement. Finally, of the 8 articles studied from the philosophical aspect, 6 articles reported agreed and reported disagreements as many as 2 articles. The conclusions are sourced from research and information collected from the results until it can be concluded that E-Sport is a sport, has positive issues in the social aspect, as well as sports philosophy, but sourced from the results of E- sport has shortcomings in the part of the physiolgic aspect is the problem of changing body functions to negative and addicted to games if you cannot control a healthy lifestyle balance.